Pengembangan otomasi perpustakaan Universitas Islam Negeri Sumatera Utara Medan berbasis (RADIO FREQUENCY IDENTIFICATION) - triana santi (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2019)
This paper describes the development of RFID-based Medan North Sumatra State University (UINSU) library. The development of RFID in the UINSU library is part of an effort in making efforts to increase libraries to become effective and efficient libraries in the education process. RFID is a technology that is very useful and has strengths and strengths or also called "powerful emerging technology" because an institution or college can achieve the totality of a service and management. The development of RFID-based UINSU library automation is currently very much needed by the library and UINSU Medan users. The development of RFID-based automation makes it easy for library staff to improve librarian performance in the use of information technology. The development of RFID-based library automation is also felt by the users so that it is easy in the circulation service both lending and returning books. Keywords: RFID, library, technology.